2021
DOI: 10.1186/s12889-021-10605-2
|View full text |Cite
|
Sign up to set email alerts
|

Population migration, spread of COVID-19, and epidemic prevention and control: empirical evidence from China

Abstract: Background This study applied the susceptible-exposed-infectious-removed (SEIR) model to analyze and simulate the transmission mechanisms of the coronavirus disease 2019 (COVID-19) in China. Methods The population migration was embedded in the SEIR model to simulate and analyze the effects of the amount of population inflow on the number of confirmed cases. Based on numerical simulations, this study used statistical data for the empirical validatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…China’s epidemic prevention and control and economic recovery have achieved positive results [ 12 , 41 ]. China has a population of over 1.4 billion.…”
Section: Discussionmentioning
confidence: 99%
“…China’s epidemic prevention and control and economic recovery have achieved positive results [ 12 , 41 ]. China has a population of over 1.4 billion.…”
Section: Discussionmentioning
confidence: 99%
“…However, as our knowledge about COVID-19 has increased with time, it can be used as a reference for the prevention and control of other infectious diseases in the future. Second, there were not enough months of monitoring data since the COVID-19 pandemic started because China has taken strict prevention and control measures to greatly reduce the traffic of international travelers after May 2020 ( 9 ). In addition, there were no data of the COVID-19 infection in people having common infectious diseases because we had no authority to detect the infection of common infectious diseases of travelers transferred to the hospital immediately due to the diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done effectively as the pathogens of these diseases are clear and established detection methods are available ( 7 , 8 ). Although the source and route of transmission of different infectious diseases from infected people are different, the human-to-human spread of viruses usually occurs via droplets, sweat, blood, and other body fluids through contact or airborne transmission ( 9 , 10 ). In particular, understanding the epidemic characteristics of infectious diseases that are common among international travelers will help understand the regional and population differences thereof, understand the demographic and geographical characteristics of infectious patients leaving and entering China, and define the infectious disease prevention and control level of different countries.…”
Section: Introductionmentioning
confidence: 99%
“…As to environmental factors, a study indicated temperature and the columnar density of total atmospheric ozone had a strong association with the tendency of COVID-19 spreading in almost all states in the USA [ 54 ]. As for regulations mainly including mobility restrictions and other non-pharmacological interventions, ill-prepared work [ 55 ], facemask shortage [ 56 ], poor traveller screening [ 57 ], forgone care [ 58 ], and population migration [ 59 ] could lead to ineffective prevention and controlling COVID-19. Regarding progressing stages, changes of COVID-19 ND, NH, NR, and NC might be caused by COVID-19 epidemic progressing laws differentially in various countries.…”
Section: Discussionmentioning
confidence: 99%